Analisis Implementasi Bimbingan Konseling Komprehensif di Sekolah (Sebuah Tinjauan Teoritis dan Praktis) - Irawan, Sapto; Ramli, M. (JURNAL KONSELING GUSJIGANG, 2024)
Comprehensive counseling guidance is a comprehensive service. In fact, there are various dynamics in implementing comprehensive guidance and counseling services in schools. The aim of this research is to examine the implementation of comprehensive guidance and counseling in depth from both theoretical and practical concepts based on the results of recent research. This research method is a literature review, which is sourced from various reading materials and research results. The results of the study can be explained that: Comprehensive guidance and counseling consists of four main components, namely: basic services, responsive services, individual planning, and system support. Guidance and counseling teachers need understanding and ability to design, implement and evaluate it. Comprehensive guidance and counseling in its implementation needs to involve related parties both within the school and outside the school environment. The development of comprehensive counseling programs and services can be carried out by integrating technological advances. The recommendation from the study is that it is necessary to increase teacher capacity in comprehensive guidance and counseling and integrating technology.